MODERASI BERAGAMA DALAM PENDIDIKAN AGAMA ISLAM DI INDONESIA PERSPEKTIF AL-QUR'AN DAN HADIS DALAM ERA GLOBALISASI - nyakcut; Zulkarnaini; Mustamar Iqbal Siregar (LPPM Institut Nida El-Adabi, 2024)
This article aims to analyze the concept of religious moderation in Islamic Religious Education (PAI) in Indonesia and its role in fostering a generation that is tolerant, inclusive, and morally upright. This study employs a qualitative method with a literature review approach, examining primary and secondary sources. The findings reveal that religious moderation serves as a crucial strategy in addressing the challenges of radicalism and intolerance. In PAI, religious moderation is implemented through the principles of justice, balance, and tolerance, which are integrated into the development of a multicultural curriculum and extracurricular activities based on the values of rahmatan lil alamin. Literature studies indicate that the principles of religious moderation are rooted in Islamic teachings, such as the concept of ummatan wasathan (a just and balanced community) in Surah Al-Baqarah verse 143, which emphasizes the importance of being a fair and balanced community. Additionally, the Hadith of Prophet Muhammad (SAW) underscores simplicity and tolerance in practicing religion. Grounded in the Qur’an and Hadith, religious moderation in PAI serves as a fundamental framework for establishing a harmonious and multicultural society.